Selected publications - Garhammer, J.
Übersicht zu ausgewählten Publikationen zu trainingswissenschaftlichen Fragen des Gewichthebens und des Krafttrainings von J. Garhammer mit Zugriff auf die Originaltexte: BOOKS & BOOK CHAPTERS Garhammer, J. and B. Takano. "Training For Weightlifting". In: Strength and Power in Sport (P.V. Komi, ed.), THE ENCYCLOPEDIA OFSPORTSMEDICINE, Volume 3, Blackwell Scientific Publications, Oxford, England. Chapter 16, pp. 357-369, 1992. [ Revised Edition - Chapter 25, pp. 502-515, 2003. ] ** Garhammer, J. "Weight Lifting & Training" (Chapter 5, pp.169-211). In: Biomechanics of Sport (C.L. Vaughan, ed.), CRC Publishers, Inc., Boca Raton, FL., 1989. Garhammer, J. Sports llustrated - StrengthTraining. Harper & Row Publishers, New York, 1986. Second Printing, Time, Inc., 1987. Chapter 2. Chapter 5. Chapter 7. REFEREED RESEARCH JOURNAL ARTICLES ** Garhammer, J. "A review of power output studies of Olympic and Power lifting: Methodology, performance prediction, and evaluation tests". J. Strength & Conditioning Research (formerly J. Appl. Sport Sci. Research) 7(2): 76-89,1993. Garhammer, J., and R. Gregor. "Propulsive forces as a function of intensity for weightlifting and vertical jumping". J. Appl. Sport Sci. Research 6(3):129-134, 1992. Garhammer, J. "A comparison of maximal power outputs between elite male and female weightlifters in competition". Int. J. Sport Biomechanics 7(1): 3-11, 1991. Garhammer, J. "Biomechanical profiles of Olympic weightlifters". Int. J. Sport Biomechanics 1(2): 122-130, 1985. Garhammer, J. "Energy flow during Olympic weightlifting". Med. Sci. Sports Exercise 14(5):353-360, 1982. Garhammer, J. "Power production by Olympic weightlifters". Med. Sci. Sports Exercise 12(1):54-60, 1980. APPLIED JOURNALS AND PERIODICALS Garhammer, J. "Barbell Trajectory, Velocity, and Power Changes: SIx Attempts and Four World Records." Weightlifting USA, Volume 19(3), Fall 2001, pp. 27-30. Garhammer, J. "Sport Specific Program Development: Part 1 - Biomechanical Considerations." Strength and Health on line magazine at www.yorkbarbell.com, Summer 2001, pp. 32-36. Part 2 (with E. Burkhardt and E. Labombarda) Winter / Spring 2002, pp. 13-19. Garhammer, J. "New Abdominal Training: Devices and Total Torso Conditioning." Strength and Health on line magazine at www.yorkbarbell.com, Spring 2001, pp. 13-14. Garhammer J. "How Sport and Exercise Science Can Contribute To Improve Activity Specific Training and Equipment Selection." Strength and Health on line magazine at www.yorkbarbell.com, Winter 2001, pp. 21-22. Garhammer, J. "Do you qualify to be a strength and conditioning professional?" Nat. Strength & Cond. Asso. J. 20(1):62-63, 1998. Garhammer, J. "Free weight equipment for the development of athletic strength and power". Nat. Strength & Cond. Asso. J. 3(6):24-26, 1981. ABSTRACTS Burkhardt, E., B. Barton and J. Garhammer. "Maximal impact and propulsive forces during jumping and explosive lifting exercises." J. Appl. Sports Sci. Research 4(3):107, 1990. R. Rozenek and J. Garhammer. "Male-female strength comparisons and the rate of decline with age in weightlifting and powerlifting." First International Conference on Weightlifting and Strength Training, Lahti, Finland, November 1998. Conference Book pp. 287-288. Garhammer, J., H. Kauhanen, and K. Hakkinen. "A Comparison of Performances by Women at the 1987 and 1998 World Weightlifting Championships." Science for Success Congress, Jyvaskyla, Finland, October 2002. Note: The Poster is more detailed than the Abstract. Abstract or Poster. CONFERENCE PROCEEDINGS Garhammer, J. "Weightlifting Performance and Techniques of Men and Women." First International Conference on Weightlifting and Strength Training, Lahti, Finland, November 1998. Conference Book pp. 89-94.